Promoting Stakeholder's Autonomy in the Process of Creating Educational Digital Games - Araújo, Rafael D.; Gasparini, Isabela (Companion Proceedings of the Brazilian Symposium on Computer Games and Digital Entertainment (SBGames); 2021: Companion Proceedings of the 20th Brazilian Symposium on Games and Digital Entertainment, 2021)
The process of developing educational digital games presents several challenges. Authorship is one of them, intensified by the infinity of application domains and the time-consuming process of developing and deploying each new game. Thus, there is a gap between the creative process of educational digital games and their development, causing a rupture in scale between the need to create these artifacts for specific purposes and their effective use. Thus, this work discusses the challenge of creating software architectures and ecosystems to provide more autonomy in the construction of educational digital games by different stakeholders, maintaining characteristics of an educational software and also to allow the monitoring of the learning process. For this, the paper discusses this challenge from the point of view of teachers, students and managers, and their different roles in this context.